Pharmacognostical Standardization and HPTLC fingerprint of Tribulus Terrestris l - Thenmozhi, S. (International Journal of Pharmaceutical & Biological Archive, 2017)
This herb is prostrate, annual or biennial having a length up to 90 cm. Leaves paripinnate; leaflets 4-5 pairs, subequal, 2-4 cm in length oblong to linear-oblong, mucronate, pubescent on both surfaces. This trailing plant is common in sandy soil, found throughout India, ascending to 3300 m in Himalaya, particularly common in dry and hotter parts of the country viz., Rajasthan, Gujarat, Deccan, and Andhra Pradesh. It is a traditional medicinal plant, which is valued for its hypertensive, CNS stimulant, spasmogenic, analgesic, vasodepressant, muscle relaxant, cardiotonic, diuretic, antiurolithiatic, antibacterial, antifungal, antimicrobial, molluscicidal, cytotoxic activity on FL-cells, hepatoprotective, cytoprotective and anticonvulsant. The current study was therefore carried out to provide requisite pharmacognostic details of whole plant of Tribulus terrestris L. Pharmacognostic evaluation included examination of morphological and microscopical characters; physicochemical properties, phytochemical analysis and HPTLC finger print. Phytochemical screening reported the presence of tannins, alkaloids, glycosides, steroidal compounds. The Rf values are detected at 254 nm and 366nm by qualitative densitometric HPTLC fingerprint, can be used as identifying marker for Hydro alcoholic extract. The present studies will the information with respect to identification and authentication of crude drug.